ORGANIZAÇÃO E RESISTÊNCIA DE TRABALHADORES RURAIS NA LUTA PELA TERRA NO MARANHÃO: entre a necessidade e a liberdade. - SILVA, Karênina Fonsêca (2019)
This thesis exposes the result of the analysis of the organization and resistance of rural workers in the struggle for land in the face of the industrialization project in the state of Maranhão demarcated by the condition of dependence in the process of internationalization of capital, subjecting itself to the hierarchical forms of power generated by the hegemonic countries. It analyzes the dialectics of imperialism and the subalternization of peripheral economies, in the logic of financial capital and dependent development through the (re) location of productive processes, which places the state of Maranhao on the route of major industrial projects. It configures the process of transnational industrialization in the state, with the implementation of large industrial projects and their implications in (re) productive organization in the municipality of Bacabeira. It contextualizes agrarian conflicts and the struggle for land as a central issue in the dispute between social classes, a secular problem that surrounds the agrarian question, in a fruitful field of historical, political and economic conflicts. It analyzes organization and resistance as relations of forces in the political struggle and highlights the identity and class consciousness as essential historical constructions in the process of organization, in the perspective of emancipation. It contextualizes the organization and struggle of rural workers in Brazil, highlighting the particularities in Maranhão. It analyzes the struggles, organization and resistance of the rural workers in Salva Terra and Santa Quiteria, configuring the forms and strategies used by the workers in the struggle for land, as a condition of survival, evidenced in the forms of insertion and participation in the organizational instances and their relations with the local authority represented by the Municipality of Bacabeira. It is concluded that in the dynamics of class struggle in the process of implementation of large industrial projects in Maranhão, despite the unfavorable conditions for workers in the correlation of forces between classes, rural workers remain in the confrontation, building strategies of organization, of struggle and resistance in the face of successive attacks of the great capital, represented by the great industrial projects in Maranhão.